1983
DOI: 10.1055/s-2008-1041624
|View full text |Cite
|
Sign up to set email alerts
|

Psychodynamic Understanding and Treatment of the Chronic Intractable Benign Pain Syndrome-Treatment Outcome

Abstract: Medical teaching stresses the value of a diagnosis based on changes or alterations in normal anatomy or physiology that are reflected in signs and symptoms with which the patient presents. The unfblding of' the historical sequence of the patient's signs and symptoms is of primary iniportance in the formation of a diagnosis.When there is a problem of pain, of necessity there will be a search for appropriate pathoanatomic or pathophysiologic peripheral sources of the noxious input that has resulted in the person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The results of treatment of patients with chronic pain must attend mainly to long-term results before it can be determined if there were any beneficial effects of treatment (Crue, 1983). These are difficult to perform long-term follow-up studies, and we have reported on our work (Pinsky, 1983;Pinsky et aL, 1979).…”
Section: Treatment and Treatment Outcomementioning
confidence: 73%
See 4 more Smart Citations
“…The results of treatment of patients with chronic pain must attend mainly to long-term results before it can be determined if there were any beneficial effects of treatment (Crue, 1983). These are difficult to perform long-term follow-up studies, and we have reported on our work (Pinsky, 1983;Pinsky et aL, 1979).…”
Section: Treatment and Treatment Outcomementioning
confidence: 73%
“…Furthermore, we believe this type of mechanism can explain all chronic pain syndromes in categories 5 and 6 of the classification in Table 1. This type of chronic pain syndrome has been described by us in the past (Pinsky, 1978(Pinsky, , 1983) as a chronic intractable benign pain syndrome (CIBPS). Descriptors of this syndrome are presented in Table 3.…”
Section: Central Neurologicalfeaturesmentioning
confidence: 99%
See 3 more Smart Citations